Lateral thinking: Neurodegeneration of the cortical cholinergic system in Alzheimer's disease - Crockett, Rachel A.; Casselton, Charlotte; Howard, Tatianna M.; Wilkins, Kevin B.; Seo, Gang; Brontë-Stewart, Helen M. (Neurobiology of disease, 2024)
Atrophy of the nucleus basalis of Meynert (NBM) is an early indicator of Alzheimer's disease (AD). However, reduced integrity of the NBM white matter tracts may be more relevant for cognitive impairment and progression to dementia than NBM volume. Research is needed to compare differences in NBM volume and integrity of the lateral and medial NBM tracts across early and later stages of AD progression. 187 participants were included in this study who were either healthy controls (HC; n = 50) or had early mild cognitive impairment (EMCI; n = 50), late MCI (LMCI; n = 37), or AD (n = 50). NBM volume was calculated using voxel-based morphometry and mean diffusivity (MD) of the lateral and medial NBM tracts were extracted using probabilistic tractography. Between group differences in NBM volume and tract MD were compared using linear mixed models controlling for age, sex, and either total intracranial volume or MD of a control mask, respectively. Associations between NBM volume and tract MD with executive function, memory, language, and visuospatial function were also analysed. NBM volume was smallest in AD followed by LMCI (p < 0.0001), with no difference between EMCI and HC. AD had highest MD for both tracts compared to all other groups (p < 0.01). Both MCI groups had higher lateral tract MD compared to HC (p < 0.05). Medial tract MD was higher in LMCI (p = 0.008), but not EMCI (p = 0.09) compared to HC. Higher lateral tract MD was associated with executive function (p = 0.001) and language (p = 0.02). Integrity of the lateral NBM tract is most sensitive to the earliest stages of AD and should be considered an important therapeutic target for early detection and intervention. •Integrity of lateral NBM tract is most sensitive to disease stage.•Integrity of lateral NBM tract decreases with greater disease severity.•Integrity of medial NBM tract is worst in AD followed by late-stage MCI.•NBM volume is smallest in people with AD followed by late-stage MCI.•Integrity of lateral NBM tract is associated with executive functions and language.